Analysis of Rheological State of SBS Modified Bitumens Based on Viscosity Measurements - Zieliński K. (Archives of Civil Engineering, 2013)
Each bitumen has a slightly different group composition, thus bitumen modification with the SBS copolymer gives slightly different results in each case. Both in the industry and construction practice there is still no simple method available which would allow the evaluation of the impact of SBS content and the group composition of bitumen on the structural and rheological properties of the polymer bitumen mix. The article presents the results of the dynamic viscosity tests of three bitumen types. Based on the analysis of the results obtained, it was found that changes in the rheological properties caused by SBS additive are characteristic for each of the bitumens tested and their chemical and group composition. They are also proportionate to the amount of the modifier added. In order to have a possibility to measure this impact, three coefficients rheologically characterizing polymer and bitumen mixes were applied.